Modeling tools for ecohydrological characterization - Sinnathamby, Sumathy (Kansas State University, 2014)
Ecohydrology, a sub-discipline of hydrology, deals with the ecological impacts of and interactions with the hydrological cycle. Changes in hydrology of the Great Plains rivers, and their impacts on water quality, water resources, aquatic ecosystems, and fish species distributions have been documented. The major goal of this study was to develop and test methods to analyze watershed-level ecohydrological characteristics. The specific objectives were (a) to detect past temporal trends and spatial variability in hydrologic indices, (b) to evaluate the presence and/or extent of spatial and temporal relationships between climatic and ecohydrological variables and riverine historical data on fauna species density and distribution, and (c) to assess model calibration strategies for accurate ecohydrological indicator simulation. The Kansa River Basin (KRB), which has substantial land use, soil and climate variability, as well as variation in anthropogenic drivers (dams, diversions, reservoirs, etc.), was the focus of this study. Thirty eight hydrological indicators were generated using the indicators of hydrologic alterations software for 34 stations in the KRB using 50-year streamflow records and trend analysis using Mann-Kendall, Seasonal Kendall, and Sen’s slope estimator tests. Across the KRB a decreasing trend was evident for annual mean runoff, summer and autumn mean runoff, 30-day, 90-day minimum flows, and 1-day, 3-day, 7-day, 30-day and 90-day maximum flows. Most of the significant negative trends were observed in the High Plains ecoregion. Two hydrologic indicators, high-flow pulse count and mean summer streamflow, were significantly different in streams that lost two indicator fish species, indicating that changes in streamflow have altered the fish habitat of this region. The Soil and Water Assessment Tool (SWAT) biophysical model calibrated using a multi-objective framework (multi-site, multivariable and multi-criteria) was able to simulate most of the ecohydrological indicators at different hydrological conditions and scales. The SWAT model provided robust performance in simulating high-flow-rate ecohydrologic indicators. However ecohydrologic indicators performance was highly dependent on the level of calibration and parameterization. The effect of calibration and parameterization on ecohydrologic indicators performance varied between watersheds and among subwatersheds.
Keywords: Ecohydrological indicators; Soil and water assessment tool; Modeling; Kansas River Basin; Ecology (0329); Environmental Engineering (0775); Water Resource Management (0595)